Negative regulation of abscisic acid-induced stomatal closure by glutathione in Arabidopsis - Md. Sarwar, Jahan; Okuma, E1; Munemasa, S; Hossain, MA
We found that glutathione (GSH) is involved in abscisic acid (ABA)-induced stomatal closure. Regulation of ABA signaling by GSH in guard cells was investigated using an Arabidopsis mutant, cad2-1, that is deficient in the first GSH biosynthesis enzyme, γ-glutamylcysteine synthetase, and a GSH-decreasing chemical, 1- chloro-2,4-dinitrobenzene (CDNB). Glutathione contents in guard cells decreased along with ABA-induced stomatal closure. Decreasing GSH by both the cad2-1 mutation and CDNB treatment enhanced ABAinduced stomatal closure. Glutathione monoethyl ester (GSHmee) restored the GSH level in cad2-1 guard cells and complemented the stomatal phenotype of the mutant. Depletion of GSH did not significantly increase ABA-induced production of reactive oxygen species in guard cells and GSH did not affect either activation of plasma membrane Ca 2+ -permeable channel currents by ABA or oscillation of the cytosolic free Ca 2+ concentration induced by ABA. These results indicate that GSH negatively modulates a signal component other than ROS production and Ca 2+ oscillation in ABA signal pathway of Arabidopsis guard cells.